PENGARUH MODEL NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS I SEKOLAH DASAR - Nuranisah, Siti (INOPENDAS: Jurnal Ilmiah Kependidikan, 2023)
This study is to describe research on the effect of the Numbered Head Together Model on Indonesian Language Learning Outcomes Grade I Elementary School Students. The subject of this research is grade I students at SD Negeri 3 Srobyong in thematic learning, especially the content of Indonesian language lessons, on Basic Competencies Detailing expressions of gratitude, apologies, pleases, and the giving of compliments, invitations, notices, orders, and instructions to others. This research uses quantitative and qualitative analysis. Data collection using interview, tests and documentation. Number Head Together (NHT) is a learning model that is applied to create group interaction through discussion with numbering on each student, at the end of the discussion students who make a presentation the number designated by the teacher is not known beforehand, this encourages students to actively discuss and solve problems. This is evidenced by the learning outcomes of 33 students from those who reached the KKM 60%, increasing to 94%. The finding of this study is that the Numbered Head Together (NHT) learning model can improve student learning outcomes.